Development and Psychometric Validation of the Brief Nurses' Practice Environment Scale and Its Relation to Burnout Syndrome and Job Satisfaction: A Study in Spanish Nurses - Sansó, Noemí; Vidal-Blanco, Gabriel; Galiana, Laura; Oliver, Amparo (Frontiers in Public Health, 2021)
Introduction: Nursing environment is a vast concept that traditionally has included a wide range of job characteristics and has been related to burnout and job satisfaction. For its measurement, the Practice Environment Scale of the Nursing Work Index (PESNWI) stands out. However, shorter instruments are needed. The purpose of the study is to develop and test the Brief Nurses' Practice Environment (BNPE) Scale. Methods: The BNPE Scale was developed and tested in a sample of 210 Spanish nurses (data collection 2018). Results: Cronbach's alpha was 0.702. The confirmatory factor analysis (CFA), with an excellent fit, offered evidence of internal validity. Regarding validity, the BNPE Scale predicted both burnout and job satisfaction. Finally, evidence pointed out a cutoff score of <12 for low levels of practice environment and a cutoff score of >15 for higher levels in practice environment. Conclusions: The BNPE Scale is a short, easy-to-use measure that could be employed in major batteries assessing the quality of healthcare institutions.